SOME WAYS TO FORM YOUTH ECOLOGICAL CULTURE - Jobborova Gulnoza Kadamovna; Газизова Назигул Слямболовна (American Journals Publishing, 2024)
This article explores various strategies for fostering an ecological culture among youth, emphasizing the importance of early education, community engagement, and policy support. The methods employed include literature review, surveys, and practical projects. The results highlight successful case studies and the effectiveness of different approaches. The discussion addresses challenges and future directions. The conclusions and suggestions provide actionable steps for educators, policymakers, and communities.
Keywords: Youth ecological culture, environmental education, sustainability, community engagement, ecological awareness, green initiatives